Cardiac mitochondrial biogenesis in endotoxemia is not accompanied by mitochondrial function recovery - Vanasco, Virginia (2014)
Mitochondrial biogenesis emerges as a compensatory mechanism involved in the recovery process in endotoxemia and sepsis. The aim of this work was to analyze the time course of the cardiac mitochondrial biogenesis process occurring during endotoxemia, with emphasis on the quantitative analysis of mitochondrial function. Female Sprague-Dawley rats (45 days old) were ip injected with LPS (10 mg/kg). Measurements were performed at 0?24 h after LPS administration. PGC-1 α and mtTFA expression for biogenesis and p62 and LC3 expression for autophagy were analyzed by Western blot; mitochondrial DNA levels by qPCR, and mitochondrial morphology by transmission electron microscopy. Mitochondrial function was evaluated as oxygen consumption and respiratory chain complex activity. PGC-1 α and mtTFA expression signiﬁcantly increased in every time point analyzed, and mitochondrial mass was increased by 20% (P 0.05) at 24 h. p62 expression was signiﬁcantly decreased in a time-dependent manner. LC3-II expression was signiﬁcantly increased at all time points analyzed. Ultrastructurally, mitochondria displayed several abnormalities (internal vesicles, cristae disruption, and swelling) at 6 and 18 h. Structures compatible with fusion/ﬁssion processes were observed at 24 h. A signiﬁcant decrease in state 3 respiration was observed in every time point analyzed (LPS 6 h: 20%, P 0.05). Mitochondrial complex I activity was found decreased by 30% in LPS-treated animals at 6 and 24 h. Complex II and complex IV showed decreased activity only at 24 h. The present results show that partial restoration of cardiac mitochondrial architecture is not accompanied by improvement of mitochondrial function in acute endotoxemia. The key implication of our study is that cardiac failure due to bioenergetic dysfunction will be overcome by therapeutic interventions aimed to restore cardiac mitochondrial function.